Rosmarinic acid ameliorates renal ischemia reperfusion damage in rats - Majid Tavafi; Hassan Ahmadvand; Ahmad Tamjidipour; Afshin Hasanvand (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: Reactive oxygen species (ROS) are the main factors in pathogenesis of renal ischemia-reperfusion (I/R) injury. Objectives: The aim of this study was to evaluate the renoprotective effect of rosmarinic acid (ROA) as an antioxidant substance against renal I/R injury. Materials and Methods: Forty male rats were divided into five groups. Group 1 control; group 2 ischemia reperfusion (I/R). Groups 3, 4 and 5 I/R treated by ROA 50, 100 and 200 mg/kg respectively. The treated groups (groups 3, 4 and 5) received ROA one hour before ischemia induction. Renal ischemia was induced by ligating of renal vessels through vascular clips. After 45 minutes of ischemia, the clips were removed to make renal recirculation (reperfusion). Twenty-four hours after the onset of reperfusion, under anesthesia blood were sampled and kidneys were removed. The serum and supernatant of renal homogenate were prepared. Serum creatinine, nitric oxide (NO) and paraoxonase (PON) were measured. The concentration of renal malondialdehyde (MDA), glutathione peroxidase (GPX), glutathione (GSH) and catalase (CAT) activity were assessed. Results: The administration of ROA, decreased serum creatinine and increased serum NO and PON compared to group 2 (P<0.05). Renal MDA, GSH, GPX and CAT activity improved significantly in animals that received ROA in comparison to group 2. Conclusion: Administration of ROA improved renal I/R injuries via inhibition of lipid peroxidation and increase of GSH, GPX, CAT, NO and PON.